Implementasi Teknologi Frontend Modern pada Website Yellowweb: Kolaborasi Booostrap 5 Framework dan jQuery - Santoso, Miftah Faroq (Lembaga Dongan Dosen, 2025)
Modern websites require responsive, interactive, and intuitive designs to ensure optimal User Experience (UX). This study examines the collaboration between the CSS Framework Bootstrap and jQuery plugins in enhancing web design quality on the Yellowweb site. By utilizing Bootstrap version 5 and jQuery plugins (Carousel, ParticleJS), the website design becomes more responsive across various screen sizes and provides interactivity to support user navigation. The findings show that this combination significantly improves user engagement and delivers a unique design that reflects the site's identity. This approach can serve as a reference for other web developers in creating better user experiences.